2009
DOI: 10.1098/rspb.2009.1156
|View full text |Cite
|
Sign up to set email alerts
|

Long-term social bonds promote cooperation in the iterated Prisoner's Dilemma

Abstract: Reciprocal altruism, one of the most probable explanations for cooperation among non-kin, has been modelled as a Prisoner's Dilemma. According to this game, cooperation could evolve when individuals, who expect to play again, use conditional strategies like tit-for-tat or Pavlov. There is evidence that humans use such strategies to achieve mutual cooperation, but most controlled experiments with nonhuman animals have failed to find cooperation. One reason for this could be that subjects fail to cooperate becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 36 publications
1
65
1
Order By: Relevance
“…The exchange of blood meals in vampire bats depends primarily on demand and previously received help [105], but a long-term relationship between social partners and frequent interactions may be prerequisites of such successful reciprocation. This has been suggested also by experimental results in zebra finches, which maintained high levels of cooperation in an iterated prisoner's dilemma game involving a time delay between the reciprocal exchange of help only when interacting with a long-term social partner [100]. Uncertainty caused by the delay of returned benefits can be reduced by a high interaction frequency, which is a common feature of close social relations and partnerships.…”
Section: Which Conditions Select For Reciprocity?mentioning
confidence: 74%
“…The exchange of blood meals in vampire bats depends primarily on demand and previously received help [105], but a long-term relationship between social partners and frequent interactions may be prerequisites of such successful reciprocation. This has been suggested also by experimental results in zebra finches, which maintained high levels of cooperation in an iterated prisoner's dilemma game involving a time delay between the reciprocal exchange of help only when interacting with a long-term social partner [100]. Uncertainty caused by the delay of returned benefits can be reduced by a high interaction frequency, which is a common feature of close social relations and partnerships.…”
Section: Which Conditions Select For Reciprocity?mentioning
confidence: 74%
“…Animals often are prosocial, displaying behaviors that result in a benefit to one another [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] even in the absence of self-benefit [16][17][18][19][20][21] (but see [22][23][24][25]). Several factors have been proposed to modulate these behaviors, namely familiarity [6,13,18,20] or display of seeking behavior [16,21].…”
Section: Discussionmentioning
confidence: 99%
“…One implication of these observations is that partner allopreening could be vulnerable to cheating, in which one partner solicits and receives allopreening but does not reciprocate. Recent experimental tests of cooperation and prisoner's dilemma in zebra finches (Taeniopygia guttata) showed that individuals engaged in a generous tit-for-tat strategy in which they cooperated in a food-sharing task even if their established partners occasionally defected (St-Pierre et al 2009). If buff-breasted wren partners engage in a similar strategy, immediate defection may be unimportant, because longterm partnerships provide a chance for future reciprocation.…”
Section: Discussionmentioning
confidence: 99%